Upaya Musyrifah Halaqoh Dalam Membimbing Sholat Jama’ah Santriwati Pontrenmu Darul Arqom Natar Lampung Selatan - Siska Ayu Febriani; Arizal Eka Putra; Khoironi; Anggi Septia Nugroho (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to analyze the efforts of musyrifah halaqoh in guiding the implementation of Dzuhur congregational prayer for female students at the Muhammadiyah Islamic Boarding School (PontrenMu) Darul Arqom Natar, South Lampung. Musyrifah plays an important role as a guide, supervisor, and role model in shaping the discipline of worship of female students. Challenges faced include fatigue of female students after academic activities and memorization, differences in individual character, and the influence of peers who lack enthusiasm. This study uses a qualitative approach with descriptive methods and was conducted at PontrenMu Darul Arqom Natar. Data were collected through observation, interviews, and documentation. The results of the study indicate that the role of musyrifah through halaqoh has a positive impact on increasing the discipline and devotion of female students in congregational prayer. Guidance efforts are carried out through role models, providing advice in halaqoh, supervision, and routine evaluation. Thus, the guidance of the musyrifah halaqoh has proven effective in fostering awareness, responsibility, and understanding among female students regarding the importance of performing congregational prayer in a disciplined and consistent manner